Linking changes in quality of life to haematologic response and survival in systemic immunoglobulin light‐chain amyloidosis. (29th January 2023) - Cohen, Oliver; Rendas‐Baum, Regina; McCausland, Kristen; Foard, Darren; Manwani, Richa; Ravichandran, Sriram; Lachmann, Helen; Mahmood, Shameem; Wisniowski, Brendan; Hawkins, Philip N.; Gillmore, Julian; Hsu, Kristen; et al.
Summary: This study reports health‐related quality of life (HRQL) among newly‐diagnosed immunoglobulin light‐chain (AL) patients ( n  = 914) treated with a bortezomib‐based regimen and its association with response depth and survival. Haematologic response/HRQL were assessed over 24 months in an ongoing, prospective study. HRQL change was calculated across haematologic/cardiac response levels. The relationship between baseline HRQL and survival was evaluated by the Cox proportional‐hazard model (PH). Shared‐random‐effects models (SREMs) estimated time‐to‐death conditional on current HRQL/longitudinal HRQL trajectory. At 3 months, there was consistent decline in 5/8 HRQL domains across all haematologic response levels. By 12 months, 3/5 declining domains improved among complete response (CR) patients. In contrast, the mean change in less‐than‐CR patients did not indicate improvement. Under the Cox PH, having a baseline HRQL score five points higher than the sample mean was associated with 20% lower mortality risk. SREMs indicated a five‐point greater HRQL score at the event time correlated with an approximately 30% decrease in mortality risk. For each one‐point increase in HRQL score trajectory slope, mortality risk decreased by approximately 88%. Only CR patients had HRQL improvement, while partial response patients had less decline but no meaningful improvements. These data show the importance of HRQL serial assessments of AL patients and its importance as an end‐point.